The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s41073-017-0037-8
|View full text |Cite
|
Sign up to set email alerts
|

Reviewer training to assess knowledge translation in funding applications is long overdue

Abstract: BackgroundHealth research funding agencies are placing a growing focus on knowledge translation (KT) plans, also known as dissemination and implementation (D&I) plans, in grant applications to decrease the gap between what we know from research and what we do in practice, policy, and further research. Historically, review panels have focused on the scientific excellence of applications to determine which should be funded; however, relevance to societal health priorities, the facilitation of evidence-informed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The British Medical Journal (BMJ) published a randomised controlled trial (RCT) of the effect of reviewer training on the quality of peer review for publication [21]. This was included here as the need for more RCTs in grant review research and in particular better training of reviewers has been voiced by others [33,70,71]. The BMJ trial showed that the efficacy of training may depend on its modality, as reviewers who were randomised into receiving training via a self-taught electronic package, and not a taught workshop, showed significant improvement in review quality (identifying more errors in manuscripts and rejecting more manuscripts for publication).…”
Section: Training Reviewers To Improve Interrater Reliabilitymentioning
confidence: 99%
“…The British Medical Journal (BMJ) published a randomised controlled trial (RCT) of the effect of reviewer training on the quality of peer review for publication [21]. This was included here as the need for more RCTs in grant review research and in particular better training of reviewers has been voiced by others [33,70,71]. The BMJ trial showed that the efficacy of training may depend on its modality, as reviewers who were randomised into receiving training via a self-taught electronic package, and not a taught workshop, showed significant improvement in review quality (identifying more errors in manuscripts and rejecting more manuscripts for publication).…”
Section: Training Reviewers To Improve Interrater Reliabilitymentioning
confidence: 99%
“…Training could also be provided to funding reviewers to enhance their competencies in assessing the knowledge translation component of funding applications. 46 Recommendation 5: Public policy should fund dissemination costs beyond peer-reviewed journals through full funding of knowledge translation activities so that research findings are communicated and disseminated to reach practitioners and decision makers. One of the main barriers to the translation and utilization of research evidence in public health practice is a disconnection between how researchers communicate and disseminate their findings (ie, peer-reviewed publications/academic journals and conferences) 47 and how practitioners and decision makers learn about the latest research evidence (eg, webinars and workshops, individual communication, social media).…”
Section: Recommendation 3: Public Policy Funding Schemes Should Suppo...mentioning
confidence: 99%
“…Training could also be provided to funding reviewers to enhance their competencies in assessing the knowledge translation component of funding applications. 46…”
mentioning
confidence: 99%
“…In the peer review section, several articles published have focused on diverse aspects of the peer review process. These span a deeper dive into how grant review panels work [ 33 ] and the need for support for peer reviewers, particular in areas of training [ 34 , 35 ] and mentoring [ 36 ]. Other topics include a study of reviewer recruitment in the field of ecology [ 37 , 38 ] and research into the views of junior hospital doctors on their understanding of models of peer review [ 39 ].…”
Section: It's All About the Researchmentioning
confidence: 99%